110k views
4 votes
Hmm it would have seem that I'm in need of help here help with this

Hmm it would have seem that I'm in need of help here help with this-example-1
User Saravanan
by
6.2k points

1 Answer

5 votes
To find out the answer,we can test it out one by one:

The original expression: 6×(2+8)=60

A. 6x(8+2)= 6x10 = 60✅

B. (6×2)+8 = 24+8 = 34

C. (8+2)x6 = 10×6 = 60✅

D. 6x2÷6×8 =12÷6×8 = 2×8 = 16

As A. and C. equals to the original expression, the answer is A. and C.
User Leansy
by
6.4k points